GARNET PERIDOTITE XENOLITHS FROM ALKALIC PICRITOID AND BASANITOID OF THE VITIM PLATEAU - Ashchepkov I.V.; Dobretsov N.L.; Kalmanovich M.A. (My University, 1988)
Finds of garnet peridotite xenoliths in Cenozoic volcanics are fairly rare. Until recently, only three such finds were known on the Vitim plateau, in Pliocene rocks of the Kandiduskha and the Yasha paleo-volcanoes. We give the results of our study of 53 more garnet xenoliths from the same localities and of over 70 xenoliths from a new site - picritic basalt tuff, cropping our in a quarry. We propose a mechanism of upper mantle transformation for the Vitim Plateau.
Keywords: Cenozoic; Pliocene; Cenozoic; Cenozoic::Neogene::Pliocene; Кайнозой; Кайнозой::Неоген::Плиоцен